2004
DOI: 10.1111/j.1365-313x.2004.02306.x
|View full text |Cite
|
Sign up to set email alerts
|

ALS3 encodes a phloem‐localized ABC transporter‐like protein that is required for aluminum tolerance in Arabidopsis

Abstract: Aluminum (Al) toxicity in acid soils is a worldwide agricultural problem that severely limits crop productivity through inhibition of root growth. Previously, Arabidopsis mutants with increased Al sensitivity were isolated in order to identify genes important for Al tolerance in plants. One mutant, als3, exhibited extreme root growth inhibition in the presence of Al, suggesting that this mutation negatively impacts a gene required for Al tolerance. Map-based cloning of the als3-1 mutation resulted in the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
257
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(276 citation statements)
references
References 36 publications
12
257
0
7
Order By: Relevance
“…This notion is further supported by the fact that alr104 and als3-1 mutants, which were previously shown to be resistant and sensitive to Al 3+ , respectively (Larsen et al, 1998(Larsen et al, , 2005, displayed the same [Ca 2+ ] cyt responses to all three trivalent cations as wild-type seedlings (Fig. 9).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This notion is further supported by the fact that alr104 and als3-1 mutants, which were previously shown to be resistant and sensitive to Al 3+ , respectively (Larsen et al, 1998(Larsen et al, , 2005, displayed the same [Ca 2+ ] cyt responses to all three trivalent cations as wild-type seedlings (Fig. 9).…”
Section: Discussionsupporting
confidence: 66%
“…NPPB alone did not evoke any [Ca 2+ ] cyt changes in the root transition zone (Fig. 8G Larsen et al, 1998) and one Al 3+ -sensitive mutant (als3-1; Larsen et al, 2005) with the YC3.60 reporter and evaluated the [Ca 2+ ] cyt response after treatment with Al 3+ , La 3+ , or Gd 3+ . We again focused our imaging on the region of the root that exhibited the biphasic [Ca 2+ ] cyt response, since this pattern of [Ca 2+ ] cyt change appears to be the most distinguishing and common feature of the trivalent cation response.…”
Section: Imaging Of Fret-sensitized Emission Allows Monitoring Of [Camentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some transporters involved in the aluminum distribution within cells have been identified. In Arabidopsis (Arabidopsis thaliana), the tonoplast-localized ATP-binding cassette (ABC) transporter Al sensitive1 (ALS1), which is involved in Al tolerance in Arabidopsis (Larsen et al, 2007), while ALS3 is responsible for movement of aluminum away from sensitive tissues for sequestration in more tolerant tissues (Larsen et al, 2005(Larsen et al, , 2007. Huang et al (2012) identified a rice (Oryza sativa) tonoplast-localized aluminum transporter, encoded by OsALS1, which is responsible for sequestration of aluminum into vacuoles and thus contributes to the internal detoxification of aluminum in rice.…”
mentioning
confidence: 99%
“…Two Al 3+ -sensitive mutants of Arabidopsis (als1 and als3) are mutated in genes that encode proteins of the ABC transporter family [35,36]. The functions and substrates of ALS1 and ALS3 are not known but from the mutant phenotypes, Larsen et al [35,36] inferred that the proteins act to mobilise and sequester Al 3+ within the plant to confer tolerance. ALS1 is located at the tonoplast and the gene is expressed primarily in root apices and the vascular system.…”
Section: The Als Genes Encoding Abc Transportersmentioning
confidence: 99%